1993
DOI: 10.1007/bf00206151
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the occipital condyles: report of four cases and review of the literature

Abstract: Fractures of the occipital condyle are rare; 32 cases have been reported in the literature. Here, the authors describe four additional cases of occipital condylar fracture. Anderson's classification is used: type I fracture: comminution of the condyle without significant displacement; type II: basilar fracture extending into the condyle; type III: condylar avulsion. The possible mechanisms are identified. Computed tomography proved essential in diagnosing these fractures; coronal reconstructions together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…OCFs are often overlooked in both clinical and autopsy settings. According to the currently available medical literature, CT scans are considered superior to conventional radiography [3, 2022] when it comes to diagnosing OCFs. The widespread use of CT in clinical practice has caused this injury (once considered rare and occurring in less than 1% of traumatic cases [3]), to be detected more often in patients hospitalized after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…OCFs are often overlooked in both clinical and autopsy settings. According to the currently available medical literature, CT scans are considered superior to conventional radiography [3, 2022] when it comes to diagnosing OCFs. The widespread use of CT in clinical practice has caused this injury (once considered rare and occurring in less than 1% of traumatic cases [3]), to be detected more often in patients hospitalized after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A case of bilateral OCF type I was reported by Clayman et al, 7 but neither the therapy nor the outcome was reported. Bettini et al 11 described a patient with a leftsided OCF type III and right-sided OCF of unreported grade. Once again neither the therapy nor outcome were reported.…”
Section: Discussionmentioning
confidence: 97%
“…Axial CT with sagittal and coronal reconstructions should be considered the standard of care in any patient in which this type of injury is suspected. 33,34 It should also be kept in mind that CT provides valuable information with regard to the osseous anatomy and alignment, but it is a poor imaging modality for soft tissue structures. Therefore CT is the best imaging modality for OCF, but in patients with normal CT imaging and suspected ligamentous injury, MRI is the imaging modality of choice.…”
Section: Radiological Featuresmentioning
confidence: 99%